Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1074/jbc.271.16.9209
|View full text |Cite
|
Sign up to set email alerts
|

The Major Site of Photoaffinity Labeling of the γ-Aminobutyric Acid Type A Receptor by [3H]Flunitrazepam Is Histidine 102 of the α Subunit

Abstract: The alpha subunit of the gamma-aminobutyric acid type A (GABA(A)) receptor is known to be photoaffinity labeled by the classical benzodiazepine agonist, [3H]flunitrazepam. To identify the specific site for [3H]flunitrazepam photoincorporation in the receptor subunit, we have subjected photoaffinity labeled GABA(A) receptors from bovine cerebral cortex to specific cleavage with cyanogen bromide and purified the resulting photolabeled peptides by immunoprecipitation with an anti-flunitrazepam polyclonal serum. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 23 publications
(19 reference statements)
2
69
0
1
Order By: Relevance
“…Photoaffinity labeling has successfully been used to locate the benzodiazepine (Davies et al, 1996;Duncalfe et al, 1996;Sawyer et al, 2002;Wieland et al, 1992) and muscimol (Smith & Olsen, 1994) binding sites on the GABA A receptor, and sites for etomidate (Husain et al, 2006;Ziebell et al, 2004) and octanol (Pratt et al, 2000) on the Torpedo nicotinic acetylcholine receptor. In principle photoaffinity labeling techniques should provide a comprehensive search of all possible protein targets and should not be confounded by either multiple regions of protein contributing to a binding site or by the existence of multiple binding sites.…”
Section: E Insights From Photoaffinity Labelsmentioning
confidence: 99%
“…Photoaffinity labeling has successfully been used to locate the benzodiazepine (Davies et al, 1996;Duncalfe et al, 1996;Sawyer et al, 2002;Wieland et al, 1992) and muscimol (Smith & Olsen, 1994) binding sites on the GABA A receptor, and sites for etomidate (Husain et al, 2006;Ziebell et al, 2004) and octanol (Pratt et al, 2000) on the Torpedo nicotinic acetylcholine receptor. In principle photoaffinity labeling techniques should provide a comprehensive search of all possible protein targets and should not be confounded by either multiple regions of protein contributing to a binding site or by the existence of multiple binding sites.…”
Section: E Insights From Photoaffinity Labelsmentioning
confidence: 99%
“…Consistent with this view are 2 recent reports of behavioral EtOH antagonist activity of Ro15-4513/flumazenil congeners named RY024 and RY023, that have a cyano-or an acetylene -instead of an azido -group at the C7 position of the BZ ring (McKay et al, 2004;Cook et al, 2005). In addition, it has been shown that the C7 position in classical benzodiazepines is close to the a critical histidine residue in GABA A R α1,2,3,5 subunits (α1-H101) (Berezhnoy et al, 2004) that is required for sensitivity of GABA A R to classical benzodiazepines in vitro (Wieland et al, 1992;Benson et al, 1998) and in vivo (Rudolph et al, 1999) and photolabeled by [ 3 H]flunitrazepam (Duncalfe et al, 1996). The residue homologous to this histidine is an arginine (R100) in α4 and α6 GABA A R subunits, and as described above in Section 2.5, leads to increased EtOH sensitivity of β3 and δ subunitcontaining receptors in vivo and in vitro .…”
Section: A Gaba a Receptor Ligand The Benzodiazepine Ro15-4513 Is Amentioning
confidence: 99%
“…Mutagenesis studies identified the cleft between a and c subunits as the binding pocket for benzodiazepines [12][13][14]. a 1 H101 was identified as the target of photoaffinity labeling by [ 3 H] flunitrazepam [15] and a 1 Y209 as the target of [ 3 H] Ro15-4513 [16]. Pharmacophore modeling attempted to describe the shape of the binding pocket [17,18].…”
Section: Introductionmentioning
confidence: 99%